Le ceramiche a vernice nera italica dei livelli di fondazione di Olisipo e Valentia (140–130 a.C.) - Pimenta, João; Ribera i Lacomba, Albert; Soria, Vincenzo (Rei Cretariae Romanae Fautorum Acta, 2022)
The most part of the black gloss pottery from foundation levels of Olisipo and Valentia are of italic origin such as the numerous amphorae (Greco-italic and Dr. 1A forms) and the kitchen set of dishes. In the black gloss pottery group, it is overwhelming the presence of the products from Neapolis (Campanian A) whit small amount of other black gloss products: Etruscan, ancient Cales, Byrsa 401 and others. The repertoire analysed is similar to the ones exhumed in the shipwrecks of Giannutri (150–140 BC) and Illa Pedrosa (140–130 BC). The last levels of Carthago (146 BC) and Numancia (133 BC) are also considered good indicators for the contexts under study.